Book Review:B. BITTON-ASHKELONY - D. KRUEGER, Prayer and Worship in Eastern Christianities, 5th to 11th Centuries, Routledge 2017. - TSIRONI, Niki (Byzantina Symmeikta, 2020)
Book Review:B. Bitton-Ashkelony - D. Krueger, Prayer and Worship in Eastern Christianities, 5th to 11th Centuries, Routledge 2017, pp. xvii+ 312